Efektivitas Pemantauan Penderita Terkonfirmasi Penyakit Corona Virus Disease-19 Di Kecamatan Ilir Barat I Kota Palembang - Sandy, Amiruddin; Hotlan, Mariana (@-Publik: Jurnal Administrasi Publik, 2022)
Effectiveness Monitoring of confirmed cases of COVID-19 in Ilir Barat I District, Palembang is carried out by monitoring patients independently, in close contact with the use of smartphone applications. The use of smartphone applications can affect compliance to self-isolate or be regulated automatically through the smart phone application. The problems faced include the lack of coordination to monitor patients with confirmed COVID-19 between monitoring officers and health workers at the Puskesmas Ilir Barat I Palembang, and the lack of human resources capacity to monitor patients with confirmed COVID-19 disease using the SILACAK application. This study aims to determine the effectiveness of monitoring the COVID-19 disease in Ilir Barat I District, Palembang. This research is measured by the indicators of Organizational Effectiveness theory according to Duncan (1985) which consists of three dimensions as follows: Goal Achieving, Integration and Adaptation. Judging from the results of interviews and observations made that the Monitoring of Patients with Confirmed COVID-19 Disease in Ilir Barat I District, Palembang has been running effectively and efficiently. Achieving the Goal in this case Monitoring of Patients with Confirmed COVID-19 Disease in Ilir Barat I District, Palembang has coordinated the examination of confirmed COVID-19 disease. The ability of HR who conducts Puskesmas surveillance does not yet have the expertise because of the training provided to previous officers and still requires direct training by providing material related to contacts as a media for reporting confirmed COVID-19. Achievements and Targets Monitoring of confirmed cases of COVID-19 in Ilir Barat I District, Palembang has reached 80% of confirmed cases of COVID-19 through the contact SILACAK application